Walking with individualized 3D-printed minimal footwear increases foot strength and produces subtle changes in unroll pattern - Allen, Alexandra; Pinheiro, Manuel; Schoenmaekers, Raf; D’Août, Kristiaan; Willems, Catherine (Frontiers in Ecology and Evolution, 2023)
Introduction This 5-month follow-up study, involving 66 subjects (38 intervention, 28 control; 34 females, 32 males), evaluated the biomechanics of walking while wearing bespoke, 3D-printed footwear. Methods A 3D scanner was used to obtain foot shape, which was subsequently modified to yield a suitable instep and additional room in the forefoot and toe areas, to allow for potential shape changes of the foot. Shoes were manufactured using TPU laser sintering. Pre (T0) and post (T1) the intervention, plantar pressures were collected using a plantar pressure plate (3 trials per foot) and toe flexor strength (5 trials per foot) was measured using a dynamometer, for control and intervention groups. Plantar pressure peak patterns and center-of-pressure (CoP) timing was analysed using 2D and 1D Statistical Parametric Mapping, respectively. Toe strength changes were expressed in percent and per individual as: 100 x ((strength@T1strength@T0) / strength@T0). Results Peak pressure distribution did not differ between control and intervention populations, or between T0 and T1. Center-of-pressure unroll differed between barefoot and shod conditions at T0 for the intervention group. When barefoot, the intervention group at T1 showed a more lateral CoP in early stance and a more anterior CoP in late stance compared to T0. In the intervention group, toe strength increased significantly by 48.5% between T0 and T1. Discussion Overall, the results indicate that the bespoke, 3D-printed footwear did not significantly affect peak pressure distribution compared to barefoot walking. However, center-of-pressure patterns during gait were influenced, particularly in the intervention group, with analysis indicative of barefoot subjects' CoP moving faster in early and mid-stance than when shod. Additionally, the intervention led to a significant increase in toe strength. These findings contribute to our understanding of the biomechanical effects of customized 3D-printed footwear and highlight the potential benefits of such interventions in improving foot function and strength.